The lemonade crime - Davies, Jacqueline, 1962- (Davies, Jacqueline, 1962- Lemonade war series., 2011)
When money disappears from fourth-grader Evan's pocket and everyone thinks that his annoying classmate Scott stole it, Evan's younger sister stages a trial involving the entire class, trying to prove what happened.